Assessment of Proximate, Vitamins, Minerals and Anti-nutrients Compositions of Unprocessed Vigna aconitifolia (Moth Bean) Seeds - Chinazum Immaculate Opara; Anthony Cemaluk C. Egbuonu; Chiemeziem A. Obike (Archives of Current Research International, 2017)
Proximate, vitamins, minerals and anti-nutrients compositions of unprocessed Vigna aconitifolia (moth bean) were assessed using standard procedures. Proximate compositions (%) of the sample were moisture, protein, fibre, fat, ash and carbohydrate, respectively were 12.87, 14.06, 3.52, 0.33, 3.52, 2.81 and 66.4 while vitamin (mg/100 g) contents were Vitamin A (14.65IU) Thiamin (0.23), Riboflavin (0.45) Niacin (0.47), Ascorbic acid (42.25) and Tocopherol (0.25). The mineral contents (mg/100 g) of the sample were: Potassium (51.57), Sodium (37.20), Magnesium (18.44), Calcium (16.38) Zinc (2.48), Iron (1.49), Cadmium (0.00), Lead (0.00) and Mercury (0.00) while the anti-nutrient (mg/100 g) contents were: Alkaloid (2.03), Saponin (0.65), Tannin (2.89), Flavonoids (1.31), Cyanide (0.45), and Phenols (0.15). Thus, raw Vigna aconitifolia seeds are devoid of known toxicants (lead, mercury and cadmium) and could serve as a good source of nutrients notably carbohydrate, protein, ascorbic acid, vitamin A, potassium, sodium and flavonoids. Further studies including on processing and on toxicological evaluation in animal models are warranted and recommended.